DEVELOPMENT OF STUDENT ACTIVITY SHEETS (SAS) ORIENTED ON PROJECT BASED LEARNING (PJBL) TO IMPROVE STUDENTS' CREATIVE THINKING SKILLS ON GREEN CHEMISTRY MATERIAL - Liza Nurrahma Dwi Agustin; Mitarlis (UNESA Journal of Chemical Education, 2026)
The purpose of this study was to produce student activity sheets (SAS) of project based learning to improve student’s creative thinking skills. This research used the Research and Development (R&D) method. with a 4D model, which includes the definition stage, design stage, development stage, and dissemination stage, but in this study, it was limited into the development stage. In this study, limited trials were conducted on 34 tenth grade high school students who had previously studied green chemistry material. The feasibility of the student activity sheets was reviewed in terms of validity, practicality, and effectiveness. The validity aspect obtained a mode of 4 with a good category. The practicality aspect, which was observed from the student response questionnaire, student activities, and implementation, obtained percentages of 96,9%, 95,5%, and 100%, respectively. The effectiveness aspect was reviewed from the improvement in students' creative thinking skills, the results of the improvement of creative thinking skills are stated with an average n-gain score of ≥ 0,7 in the high category. These results were also supported by the Wilcoxon test, which obtained a significance of 0,000 < 0,05. Based on its validity, practicality, and effectiveness, the student activity sheets (SAS) developed is suitable for use as a learning media.